PLANT POPULATION AND SRI MANAGEMENT ON CROP-WEED COMPETITION IN RICE IN THE HUMID TROPICS OF KERALA, INDIA - P.V. Sindhu, George C. Thomas and C.T. Abraham (Indian J. Agric. Res.., 2013)
Studies to assess the influence of plant population and management under the System of Rice Intensification (SRI) on crop-weed competition was conducted in farmer’s field at Thrissur district, Kerala, during the second crop seasons (rabi) of 2005-06 and 2006-07. The experiment was laid out in split plot with two mainplot treatments of weeding and unweeding and five subplot treatments of spacing and management. Increase in crop density under closer spacing significantly reduced the number and dry matter production of weeds. Cono weeding was not effective in controlling weeds growing very close to the rice plants. Number and dry matter production of weeds were higher in SRI plots. The uptake of nutrients by weeds was minimum in closer spacing. Weed control efficiency was also maximum for closer plant spacing of 10 cm x 10 cm. The highest grain yields of 8858 kg/ha and 8358 kg/ha during first and second years of study were observed in closer spacing of 10 X 10 cm followed by 20 x 10 cm both under normal package of practices with weeding. The yield obtained from 20 x 10 cm plots with weeding and 10 cm x 10 cm without weeding were on par showing the importance of closer spacing as a weed management strategy. Among the weeded plots, the lowest grain yield of 5250 kg/ha was observed in SRI plots with cono weeding. Uptake of nutrients by the crop was higher in plots with closer spacing with weeding.